The Evolution of Cloud Computing: Key Trends Shaping the Next Decade - Girish Poojar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article examines the transformative trends shaping cloud computing adoption over the next decade. The article explores key developments, including the rise of hybrid and multi-cloud architectures, integration of artificial intelligence and machine learning capabilities, advancement of edge computing solutions, enhancement of security frameworks, and emergence of sustainable computing initiatives. The article demonstrates how these innovations are fundamentally changing how organizations approach their technology infrastructure, highlighting improvements in operational efficiency, security posture, and environmental sustainability. The article provides insights into technical implications for organizations, emphasizing the importance of architecture modernization, security enhancement, and operational excellence in achieving successful cloud transformation.
Keywords: Cloud Computing Evolution; Hybrid Multi-Cloud Architecture; Edge Computing Integration; Security Automation; Sustainable Computing